Evaluasi Pelayanan Penumpang di Terminal Pelabuhan Merak Lintas Penyeberangan Merak-Bakauheni - Agustina, Rohma; Siahaan, Langas Denny; Sihombing, Sarinah; Raga, Paulus (Institut Transportasi dan Logistik Trisakti, 2025)
Every year, the ferry port counter system, transportation arrangement from the dock to the ship and vice versa, departure schedules, human resources, and dock facilities are undergoing improvements that should in line with the population development, socio-economic and tourism activities, and the flow of urbanization. There are two dissatisfied services in Merak Ferry Port experienced by the passengers; the safety and security services. The aim of the research is to determine the passengers’ satisfaction level of the service performance, the service facilities availability level, and the service performance of Merak Ferry Port. The data was analysed using Customer Satisfaction Index and Importance Performance Analysis with 120 ferry passengers as samples. The results of the research show that the passengers are very satisfied with the service indicators provided, hence, there are primary service indicators need improving. Three aspects that need improvements are the ease of services, the passengers’ comfortability, and the information availability of ships’ departure and arrival.